Business analytics for managers : - Laursen, Gert H. N. (John Wiley & Sons, 2017)
In this second edition of Business Analytics for Managers, the authors provided an updated look at business analytics, focusing mainly on the subject of "big data" and the increased use of analytical information in real time processes. Though the 1E touches on these two subjects, there are new terms and theories in the analytics world that need to be reflected and made explicit in a second edition. Topics covered include: - Growing open-source technologies like Hadoop and their strengths and weaknesses compared to the traditional way of storing and processing data in a data warehouse - The impact of social media. Social media has both become a new data source that can be used for multiple analytical purposes, as well as a channel to deploy analytical results in. - Data security - Cloud technologies, and - Future trends